2005
DOI: 10.1369/jhc.4a6539.2005
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR- and CD11c-positive Dendritic Cells Penetrate beyond Well-developed Epithelial Tight Junctions in Human Nasal Mucosa of Allergic Rhinitis

Abstract: The epithelial barrier of the upper respiratory tract plays a crucial role in host defense. In this study, to elucidate whether there is antigen monitoring by dendritic cells (DCs) beyond the epithelial tight-junction barrier in allergic rhinitis, we investigated the expression and function of tight junctions and characterized DCs in the epithelium of nasal mucosa from patients with allergic rhinitis. In reverse transcription-polymerase chain reaction, mRNAs of tight-junction proteins occludin, JAM-1, ZO-1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 33 publications
(60 reference statements)
9
105
0
1
Order By: Relevance
“…2 This dynamic regulation is important as it determines the trafficking patterns of ions, proteins and even the penetration of the dendrites of Langerhans or dendritic cells. 3,4 Not so long ago, the mere existence of epidermal TJs was debated but now the controversy is their relative importance for epidermal barrier function. For a long time, the dominant concept was that the paracellular flux of ions, water and solute in the epidermis was exclusively regulated by the intercellular lipid present within the SC (for a review see 5 ).…”
Section: Tight Junctions -The Under-appreciated Epidermal Barrier Strmentioning
confidence: 99%
See 2 more Smart Citations
“…2 This dynamic regulation is important as it determines the trafficking patterns of ions, proteins and even the penetration of the dendrites of Langerhans or dendritic cells. 3,4 Not so long ago, the mere existence of epidermal TJs was debated but now the controversy is their relative importance for epidermal barrier function. For a long time, the dominant concept was that the paracellular flux of ions, water and solute in the epidermis was exclusively regulated by the intercellular lipid present within the SC (for a review see 5 ).…”
Section: Tight Junctions -The Under-appreciated Epidermal Barrier Strmentioning
confidence: 99%
“…This is also observed in the gut and airways where DCs can establish transient TJs with the neighboring epithelial cells while penetrating the epithelial barrier to uptake antigens. 4,63 Importantly, in the gut, cldn-1 and occludin are expressed on DC cell membranes at baseline and ZO-1 expression can be rapidly induced following stimulation. 63 In the epidermis, LCs express cldn-1 64 and JAM-A 65 at baseline (Representative staining of cldn-1 and CD1a [LCs marker] in human epidermis is shown in Fig.…”
Section: Tj and Adaptive Immune Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Takano et al demonstrated a different way for DCs to sample allergen without disrupting the TJs. In biopsies taken from human allergic subjects, HLA-DR+ and CD11c + DCs expressed claudin-1 and penetrated beyond occludin in the epithelium of the nasal mucosa (53). Interestingly, this process was only seen in allergic individuals, and not in healthy ones.…”
Section: Pathways Of Antigen Uptake In the Respiratory Tractmentioning
confidence: 96%
“…Studies have shown that epithelial cells stimulated with DEPs release cytokines such as IL-6, IL-8, GM-CSF, and sICAM (51). The exposure of epithelial cells from allergic subjects to DEPs and tobacco contributed to a greater constitutive and pollutant-induced release of pro-inflammatory chemokines (53). Epithelial cells may therefore play an important role in mediating the effects of air pollutants on the inflammatory response in the airways.…”
Section: The Airway Epitheliummentioning
confidence: 99%